An ab initio and density functional theory study of radical-clock reactions - Jäger, Christof; Hennemann, Matthias; Mieszala, Andrzej; Clark, Timothy (Journal of Organic Chemistry, 2008)
Density functional theory (DFT) and ab initio (CBS-RAD) calculations have been used to investigate a series of "radical clock" reactions. The calculated activation energies suggest that the barriers for these radical rearrangements are determined almost exclusively by the enthalpy effect with no evidence of significant polar effects. The ring-closure reactions to cyclopentylmethyl radical derivatives and the ring opening of cyclopropylmethyl radicals give different correlations between the calculated heat of reaction and barrier, but the two types of reaction are internally consistent.